Community Forest Management in Madhya Pradesh - the Future Challenge? - Dasgupta, Saibal (Indian Forester, 2004)
The paper highlights the establishment of Joint Forest Management (JFM) in India with particular emphasis on Madhya Pradesh. The process of JFM, which is in vogue in the state of Madhya Pradesh since early 1990s, has many laudable achievements to its credit. The first part of the paper focuses on the impact of JFMs on social, economical & ecological fronts. It also emphasizes the role of women in JFM. The author emphasizes the fact that since the foundation of a solid participatory approach has been laid in the state of Madhya Pradesh and a process of social change is taking place in the state, it is perhaps time to think in terms of Community Forest Management (CFM), at least in those communities, which are functioning in an effective manner. The author, however, cautions against over enthusiasm in this transformation, as not all JFMCs are functioning effectively. The process of transformation is a slow and gradual process and can be achieved only through proper implementation of the JFM program involving all stakeholders, particularly pro-active NGOs.